ROLE OF MATHEMATICS IN CONTRIBUTING DEVELOPMENT OF CRITICAL THINKING ON STUDENTS FROM HISTORY UP TO NOW (British Journal of Global Ecology and Sustainable Development, 2025)
This scientific article presents a comprehensive methodology for enhancing the professional competence of future primary school teachers within a credit-module environment. The methodology outlined here integrates theoretical knowledge with practical skills to equip pre-service teachers with the necessary tools and competencies for successful teaching careers. By emphasizing a structured and credit-based approach, this methodology aims to foster a well-rounded educational experience that prepares future educators for the dynamic challenges of the modern classroom.